ASL UNDERPRESSURE: Gamification of American Sign Language Learning Through Human-Computer Interaction - ATIA, OSAMA; ASSKAR, HUSSAM; EL KHARCHY, OUSSAME; ELMASRY, WİSAM (IEEE, 2025)
ASL Underpressure is an innovative web-based game that utilizes video processing and deep learning models to improve the practice of American Sign Language (ASL) and bridge the communication gap between hearing and deaf communities. The game focuses on education and improving communication skills by challenging players to quickly and accurately form words using the ASL alphabet. The system incorporates a timer to maintain player engagement and allows for multiple attempts per word to encourage learning and mastery. This paper demonstrates the potential of technology to improve communication and foster understanding between diverse communities.
ICHORA 2025 - 2025 7th International Congress on Human-Computer Interaction, Optimization and Robotic Applications, Proceedings
Conference name; 7th International Congress on Human-Computer Interaction, Optimization and Robotic Applications, ICHORA 2025.
Keywords: American Sign Language; Computer Vision; Deep Learning; Video and Image Processing; Web-Based Game Development